Answer:
![A=(65)/(64)\ or\ A=1.015625](https://img.qammunity.org/2021/formulas/mathematics/high-school/21zal379iny780xi5l6at5qgbl28t84apz.png)
Step-by-step explanation:
Given:
The expression is given as:
![2^(x-6)+2^(x)](https://img.qammunity.org/2021/formulas/mathematics/high-school/n2c4jovcfkn0lqc8tfrc8lzzmhg36cjwm5.png)
The equivalent expression to the above expression is given as:
![A\cdot 2^(x)](https://img.qammunity.org/2021/formulas/mathematics/high-school/hm5vlu8oeo1vvim13y9qufgtbcurc3dk8l.png)
Now, simplifying the original expression using the law of indices:
![a^(m-n)=(a^m)/(a^n)](https://img.qammunity.org/2021/formulas/mathematics/middle-school/u333l5aq4po8hewa2f28v65h5nq9anclwa.png)
So,
. The expression becomes:
![=(2^x)/(2^6)+2^x](https://img.qammunity.org/2021/formulas/mathematics/high-school/za1fggwtj2enfj7ucuyi3hrrze260xcklm.png)
Now,
is a common factor to both the terms, so we factor it out. This gives,
![=2^x((1)/(2^6)+1)\\\\=2^x((1)/(64)+1)\\\\=2^x((1)/(64)+(64)/(64))\\\\=2^x((1+64)/(64))\\\\=2^x((65)/(64))\\\\=((65)/(64))\cdot 2^x](https://img.qammunity.org/2021/formulas/mathematics/high-school/cw38fxg7sjqcyuili9bne9mv10k4q1wdfh.png)
Now, on comparing the simplified form with the equivalent expression, we conclude:
![A\cdot2^x=((65)/(64))\cdot 2^x\\\\A=(65)/(64)\ or\ 1.015625](https://img.qammunity.org/2021/formulas/mathematics/high-school/6s71hhkgyqwqnob94akpd00v32mj7jqbck.png)
Therefore, the value of 'A' is
![A=(65)/(64)\ or\ A=1.015625](https://img.qammunity.org/2021/formulas/mathematics/high-school/21zal379iny780xi5l6at5qgbl28t84apz.png)